Les institutions financières : le défi de la T.P.S. - Cardinal, Claude (Assurances, 1991)
In his article, the author analyzes the impact of the GST on financial institutions and financial conglomerates that were created in Quebec since the beginning of 1980. He explains that while the provisions of the law are the same for all financial institutions, some may have a greater impact on operations, particularly those of life insurers.